Improvements in the crystallinity and mechanical properties of PLA by nucleation and annealing. (August 2019) - Simmons, Heather; Tiwary, Praphulla; Colwell, James E.; Kontopoulou, Marianna
Abstract: We develop strategies to improve the crystallinity and mechanical properties of PLA, without compromising its hydrolytic degradation behaviour. These include reactive extrusion, and addition of a novel type of cross-linked PLA-based nucleating agent (biofiller, BF). The crystallinity is further increased by annealing at temperatures between 80 and 120 °C. Maximum crystallinities of 55% were achieved in the presence of 7 wt% of the BF at 100 °C. The increases in crystallinity upon annealing translated to a 42% increase in the flexural modulus relative to the base PLA, while impact strength was maintained. Annealing temperatures of 100 °C are optimum, because of thermal degradation taking place above this temperature. Annealing also results in increases in the glass transition temperatures followed by improvements in the heat deflection temperature by as much as 7 °C. The nucleated and annealed PLA degraded to the same extent as the untreated PLA, when subjected to hydrolysis over a 12-week period. Graphical abstract: Image 1 Highlights: Reactive extrusion and nucleating agents were used in combination with annealing to improve the properties of PLA. A cross-linked PLA-based biofiller acts as a very effective nucleating agent. Significant improvements in crystallinity and flexural modulus were achieved. Annealing resulted in an increase in the glass transition temperature, followed by an increase in HDT. The modified PLA maintained its degradability under hydrolysis.